2022
DOI: 10.3390/jpm12101557
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Graft Function in Kidney Transplant: Risk Factors, Consequences and Prevention Strategies

Abstract: Background. Delayed graft function is a frequent complication of kidney transplantation that requires dialysis in the first week posttransplant. Materials and Methods. We searched for the most relevant articles in the National Institutes of Health library of medicine, as well as in transplantation, pharmacologic, and nephrological journals. Results. The main factors that may influence the development of delayed graft function (DGF) are ischemia–reperfusion injury, the source and the quality of the donated kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 118 publications
2
19
1
Order By: Relevance
“…To our knowledge, these results have never been described before. Interestingly, our results confirmed that factors like high donor age, elevated ischemia cold time, and high dose of norepinephrine during kidney transplant could have on impact on kidney outcome and also with the occurrence of DGF 24–29 . However, we did not find a link between hyperlactatemia and patients’ outcome, objective by 7‐day post‐operative complications.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…To our knowledge, these results have never been described before. Interestingly, our results confirmed that factors like high donor age, elevated ischemia cold time, and high dose of norepinephrine during kidney transplant could have on impact on kidney outcome and also with the occurrence of DGF 24–29 . However, we did not find a link between hyperlactatemia and patients’ outcome, objective by 7‐day post‐operative complications.…”
Section: Discussionsupporting
confidence: 68%
“…Interestingly, our results confirmed that factors like high donor age, elevated ischemia cold time, and high dose of norepinephrine during kidney transplant could have on impact on kidney outcome and also with the occurrence of DGF. [24][25][26][27][28][29] How-ever, we did not find a link between hyperlactatemia and patients'…”
Section: Discussioncontrasting
confidence: 60%
“…Inappropriate VGC dosing included underdosing and overdosing, defined as any dose below and above the predetermined eGFR ranges, respectively. Inappropriate dosing can be influenced by an early graft dysfunction, such as a delayed graft function (DGF), defined as an acute kidney injury (AKI) which occurs in the first week after transplantation or a primary non function (PNF), defined as permanent lack of graft function from the time of transplantation, both requiring a dialysis treatment [ 13 , 14 ]. CMV infection and disease were defined based on international guidelines [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The need for renal replacement therapy would fulfill the definition of delayed graft function 2 and predict inferior long-term graft and recipient survival. 3 Because immediate posttransplant graft dysfunction is largely driven by organ ischemia–reperfusion injuries, 4 it would be highly interesting to combine this approach with measures that attenuate ischemia–reperfusion injuries.…”
Section: Vitrification and Nano-warming Enable Long-term Organ Cryopr...mentioning
confidence: 99%